High-ionic-conductivity sulfide solid electrolyte and preparation method and application thereof

By adjusting the proportion of elements in the sulfide solid electrolyte, a high-ion conductivity sulfide solid electrolyte is prepared by simple ball milling and calcining method, solving the problem of low conductivity of existing sulfur-silver germanium ore-type electrolytes, achieving high efficiency and low cost improves electrochemical performance.

CN119495801APending Publication Date: 2025-02-21DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311029610.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-15
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing sulfur-silver germanium ore-type sulfide solid electrolyte has low ionic conductivity and high cost in preparation, making it difficult to achieve industrialization.

Method used

By adjusting the ratio of Li2S, GeS2, Sb2S3, Si, S, LiI, and using ordinary ball milling calcining method to prepare high-ionic conductivity sulfide solid electrolytes. The specific formula is Li(7-x)(GeSi)(1-x)/ 2SbxS5I, where 1/3≤x≤1.

Benefits of technology

It achieves high ionic conductivity and excellent electrochemical performance, reduces preparation costs, and promotes the commercial development of sulfide solid electrolytes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495801A_ABST
    Figure CN119495801A_ABST
Patent Text Reader

Abstract

The invention discloses a high-ionic-conductivity sulfide solid electrolyte and a preparation method and application thereof, the general formula of the high-ionic-conductivity sulfide solid electrolyte is Li (7-x) (GeSi) (1-x) / 2SbxS5I, and x is more than or equal to 1 / 3 and less than or equal to 1. The ionic conductivity and electrochemical performance of LPSI (lithium phosphorus sulfur iodide) of an argyrodite structure are improved mainly by adjusting the proportion of Li2S, GeS2, Sb2S3, Si, S and LiI, and then the sulfide solid electrolyte with high ionic conductivity and excellent electrochemical performance is obtained. According to the electrolyte, the P element is completely replaced by Ge, Si and Sb, so that the ionic radius is increased, a channel is provided for lithium ion transmission, and synergistic migration of lithium ions and relatively high ionic conductivity are realized. And the assembled all-solid-state battery has extremely high capacity and excellent long cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a high ionic conductivity sulfide solid electrolyte and a preparation method and application, belonging to the field of sulfide solid-state batteries. Background Art

[0002] At present, the existing solid electrolytes are mainly divided into three types: oxide solid electrolytes, sulfide solid electrolytes and polymer solid electrolytes. Sulfide solid electrolytes are considered to be the solid electrolyte material with the broadest industrial prospects due to their high ionic conductivity and processing performance. To achieve the commercial application of sulfide solid electrolytes, the prerequisite of high ionic conductivity must be met. The currently reported LGPS and LSPSCl have good ionic conductivity (~10mS cm -1 ), but its rate and long cycle performance are poor. Its tetragonal structure has poor stability and requires more pretreatment to achieve ideal electrochemical performance. In contrast, argyrodite-type sulfide solid electrolytes have a stable structure, good stability and excellent rate performance during battery cycling, and have broad application prospects. However, the ionic conductivity of argyrodite reported so far is low. Therefore, the current argyrodite sulfide solid electrolyte is still far from the goal of practical application.

[0003] In the prior art, technicians have used high-energy ball milling, plasma and other methods to prepare the corresponding solid electrolytes, but these methods are costly and difficult to truly industrialize. Therefore, it is urgent to find low-cost, simple preparation methods, and high-ionic conductivity sulfide solid electrolytes with better performance and apply them to lithium batteries. Summary of the invention

[0004] In view of the above-mentioned problems existing in the existing preparation technology, the purpose of the present invention is to propose an effective method for high ionic conductivity sulfide solid electrolyte, by ordinary ball milling calcination of raw materials Li2S, P2S5, GeS2, Sb2S3, Si, S, LiI to obtain high ionic conductivity, high ionic conductivity sulfide solid electrolyte with excellent electrochemical properties, thereby promoting its commercial development.

[0005] According to one aspect of the present application, a high ionic conductivity sulfide solid electrolyte is provided, characterized in that the general formula of the high ionic conductivity sulfide solid electrolyte is Li (7-x) (GeSi) (1-x) / 2 Sb x S5I, where 1 / 3≤x≤1.

[0006] Optionally, the general formula of the high ionic conductivity sulfide solid electrolyte is Li (7-x) (GeSi) (1-x) / 2 Sb xS5I, wherein the value of x is selected from any value among 1 / 3, 1 / 2, 2 / 3, 1, or a range between any two of the above.

[0007] Optionally, the ionic conductivity of the high ionic conductivity sulfide solid electrolyte is 1×10 -3 ~2×10 - 2 S / cm.

[0008] Optionally, the ionic conductivity of the high ionic conductivity sulfide solid electrolyte is selected from 1×10 -3 S / cm, 2×10 -3 S / cm, 3×10 -3 S / cm, 2×10 -2 S / cm or any value in the range between any two points above.

[0009] According to another aspect of the present application, a method for preparing the high ionic conductivity sulfide solid electrolyte is provided, the preparation method comprising:

[0010] A mixture containing Li2S, Sb2S3, S and LiI is ball-milled and reacted to obtain the high ionic conductivity sulfide solid electrolyte.

[0011] Optionally, the mixture also includes GeS2 and Si.

[0012] Optionally, the molar ratio of Li2S, GeS2, Si, Sb2S3, S, and LiI is: 2.5-3: 0-0.33: 0-0.33: 0.17-0.5: 1.05: 1.

[0013] Optionally, the ball milling speed is 300 to 500 rpm, and the ball milling time is 15 to 25 hours.

[0014] Optionally, the rotation speed of the ball mill is selected from any value of 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm or a range between any two of the above points.

[0015] Optionally, the ball milling time is selected from any value among 15h, 17h, 20h, 22h, 25h or a range between any two of the above points.

[0016] Optionally, pre-grinding is performed before the ball milling, the pre-grinding speed is 100 to 300 rpm, and the pre-grinding time is 1 to 2 hours.

[0017] Optionally, the rotation speed of the pre-grinding is selected from any value of 100 rpm, 150 rpm, 200 rpm, 250 rpm, 300 rpm or a range between any two of the above points.

[0018] Optionally, the pre-grinding time is selected from any value among 1 h, 1.2 h, 1.5 h, 2 h, or a range between any two of the above points.

[0019] Optionally, the reaction temperature is 400-500° C., and the reaction time is 3-7 hours.

[0020] Optionally, the reaction temperature is selected from any value of 400°C, 420°C, 450°C, 480°C, 500°C or a range between any two of the above points.

[0021] Optionally, the reaction time is selected from any value among 3h, 4h, 5h, 6h, 7h or a range between any two of the above points.

[0022] According to another aspect of the present application, there is provided a use of the above-mentioned high ionic conductivity sulfide solid electrolyte in a sulfide solid-state battery.

[0023] Optionally, the sulfide solid-state battery comprises a positive electrode, a negative electrode and a solid electrolyte;

[0024] The solid electrolyte is a high ionic conductivity sulfide solid electrolyte;

[0025] The positive electrode is selected from LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.6 Co 0.2 Mn 0.2 One of O2 and LiCoO2;

[0026] The negative electrode is selected from at least one of Li-In alloy, Li-Mg alloy and Li-Sn alloy.

[0027] This application is implemented through the following technical solutions:

[0028] A design scheme for a high ionic conductivity sulfide solid electrolyte includes the preparation of a high ionic conductivity sulfide solid electrolyte, matching of positive and negative electrodes, and structural design thereof.

[0029] The preparation method of the composite sulfide solid electrolyte is prepared by the following steps:

[0030] (1) Li2S, GeS2, Si, Sb2S3, S, and LiI in a molar ratio of 2.5-3:0-0.33:0-0.33:0.17-0.5:1.05:1 are placed in a ball mill, pre-milled at 100-300 rpm for 1-2 h, and ball milled at 300-500 rpm for 15-25 h to obtain an amorphous phase mixture of a sulfide solid electrolyte, which is cold-pressed to obtain a green embryo, placed in a quartz tube, heated to 400-500° C. at room temperature for 3-7 h, and then cooled to room temperature to obtain a ceramic phase high ionic conductivity sulfide solid electrolyte.

[0031] (2) Place 90-110 mg of solid electrolyte in a battery mold and press at 400-550 MPa for 1-3 min. 0.8 Co 0.1 Mn 0.1 O2), NCM622(LiNi 0.6 Co 0.2 Mn 0.2 O2), LCO (LiCoO2) and pressed at a pressure of 400-550 MPa for 1-3 min.

[0032] (3) One or a mixture of the cut Li-In, Li-Mg or Li-Sn alloys is placed as the negative electrode at the bottom of the battery mold, and pressed at a pressure of 20 to 50 MPa for 1 to 3 minutes, and finally its electrochemical performance is tested.

[0033] In step (2), the solid electrolyte is Li 20 / 3 (GeSi) 1 / 3 Sb 1 / 3 S5I, Li 19 / 3 (GeSi) 1 / 6 Sb 2 / 3 S5I, Li 13 / 2 (GeSi) 1 / 4 Sb 1 / 2 S5I, one of Li6(GeSi)0Sb1S5I.

[0034] The present invention discloses a method for designing, preparing and applying a high ionic conductivity sulfide solid electrolyte. This invention belongs to the field of sulfide solid-state batteries. The present invention mainly improves the ionic conductivity and electrochemical properties of LPSI (lithium phosphorus sulfur iodide) with a argyrodite structure by adjusting the ratio of Li2S, GeS2, Sb2S3, Si, S and LiI, thereby obtaining a high ionic conductivity sulfide solid electrolyte with high ionic conductivity and excellent electrochemical properties. The electrolyte completely replaces the P element with Ge, Si and Sb, thereby increasing the ionic radius, providing a channel for lithium ion transmission, and resulting in the coordinated migration of lithium ions and higher ionic conductivity. The assembled all-solid-state battery has extremely high capacity and excellent long cycle performance.

[0035] The beneficial effects of this application include:

[0036] 1) The high ionic conductivity sulfide solid electrolyte provided in the present application completely replaces P with Ge, Si, and Sb, thereby increasing the ionic radius and improving the ionic conductivity of the sulfide solid electrolyte.

[0037] 2) The high ionic conductivity sulfide solid electrolyte provided in the present application has the function of improving the ionic conductivity of the sulfur-iodine solid electrolyte by adjusting the preparation conditions.

[0038] 3) The high ionic conductivity sulfide solid electrolyte provided in the present application provides a channel for lithium ion transmission, resulting in the coordinated migration of lithium ions and higher ionic conductivity, thereby improving the electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 is Li in Example 1 of the present application 20 / 3 (GeSi) 1 / 3 Sb 1 / 3 XRD pattern of S5I.

[0040] Figure 2 is Li in Example 1 of the present application 20 / 3 (GeSi) 1 / 3 Sb 1 / 3 XRD partial magnification of S5I.

[0041] Figure 3 This is an impedance curve diagram of the high ionic conductivity sulfide solid electrolyte of Example 1 of the present application.

[0042] Figure 4 This is a rate diagram of the sulfide all-solid-state battery of Example 1 of the present application.

[0043] Figure 5 This is a long cycle performance diagram of the sulfide all-solid-state battery of Example 1 of the present application. DETAILED DESCRIPTION

[0044] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0045] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0046] This application uses a Zana electrochemical workstation to perform EIS impedance testing.

[0047] This application uses a blue electric tester to test the electrochemical performance of solid-state batteries.

[0048] The reagents or instruments used in this application without indicating the manufacturer are all conventional products that can be purchased from the market.

[0049] The room temperature in the examples of the present application refers to "25° C."

[0050] Example 1

[0051] 0.651g Li2S, 0.2279g GeS2, 0.0468g Si, 0.2831g Sb2S3, 0.1683g S, 0.6692g LiI raw materials with a molar ratio of 2.83:0.33:0.33:0.17:1.05:1 were put into a ball mill (ball to material ratio was 20:1). The amorphous phase mixture of sulfide solid electrolyte was obtained by pre-grinding at 100 rpm for 0.5h and ball milling at 450 rpm for 20h. The blank was cold pressed and placed in a quartz tube, heated to 450℃ at room temperature for 5h. The temperature was lowered to room temperature to obtain a ceramic phase high ionic conductivity sulfide solid electrolyte Li 20 / 3 (GeSi) 1 / 3 Sb 1 / 3 S5I. Weigh 100 mg of solid electrolyte and put it into the battery mold. Press it at 550 MPa for 1 min. Use Li-In as the negative electrode and NCM811 as the positive electrode at a current density of 0.1C to perform a battery long cycle test. The test shows that the battery cycled 100 times and the capacity remained at 175 mAh g -1 .like Figure 1 and Figure 2 Shown is Li 20 / 3 (GeSi) 1 / 3Sb 1 / 3 XRD pattern of S5I. Figure 1 and Figure 2 It can be seen that the narrowest lattice spacing corresponds to the smallest unit cell and the highest lithium ion concentration. Figure 3 From the impedance curve in , it can be seen that the impedance is greatly reduced and the ionic conductivity is significantly improved. Figure 4 It can be seen from the rate diagram of the sulfide all-solid-state battery that good rate performance is obtained; Figure 5It can be seen that the all-solid-state battery can run stably for 300 cycles at room temperature and 0.5C current.

[0052] Example 2

[0053] 0.632g Li2S, 0.171g GeS2, 0.0351g Si, 0.4246g Sb2S3, 0.1683g S, 0.6692g LiI raw materials with a molar ratio of 2.75:0.25:0.25:0.25:1.05:1 were put into a ball mill (ball to material ratio was 20:1). The amorphous phase mixture of sulfide solid electrolyte was obtained by pre-grinding at 100 rpm for 0.5h and ball milling at 450 rpm for 20h. The blank was cold pressed to obtain a blank, placed in a quartz tube, and heated to 450℃ at room temperature for 5h. The temperature was lowered to room temperature to obtain a ceramic phase high ionic conductivity sulfide solid electrolyte Li 13 / 2 (GeSi) 1 / 4 Sb 1 / 2 S5I. Weigh 100 mg of solid electrolyte and put it into the battery mold. Press it at 550 MPa for 1 min. Use Li-In as the negative electrode and NCM811 as the positive electrode at a current density of 0.1C to perform a battery long cycle test. The test shows that the battery cycled 100 times and the capacity remained at 168 mAh g -1 .

[0054] Example 3

[0055] 0.6127g Li2S, 0.114g GeS2, 0.0234g Si, 0.5662g Sb2S3, 0.1683g S, 0.6692g LiI raw materials with a molar ratio of 2.66:0.17:0.17:0.33:1.05:1 were put into a ball mill (ball to material ratio was 20:1). The amorphous phase mixture of sulfide solid electrolyte was obtained by pre-grinding at 100 rpm for 0.5h and ball milling at 450 rpm for 20h. The blank was cold pressed to obtain a blank, placed in a quartz tube, and heated to 450℃ at room temperature for 5h. The temperature was lowered to room temperature to obtain a ceramic phase high ionic conductivity sulfide solid electrolyte Li 19 / 3 (GeSi) 1 / 6 Sb 2 / 3 S5I. Weigh 100 mg of solid electrolyte and put it into the battery mold. Press it at 550 MPa for 1 min. Use Li-In as the negative electrode and NCM811 as the positive electrode at a current density of 0.1C to perform a battery long cycle test. The battery cycled 100 times and the capacity remained at 163 mAh g -1 .

[0056] Example 4

[0057] 0.574g Li2S, 0g GeS2, 0g Si, 0.848g Sb2S3, 0.1683g S, 0.6692g LiI raw materials with a molar ratio of 2.5:0:0:0.5:1.05:1 were put into a ball mill (ball to material ratio of 20:1). The amorphous phase mixture of sulfide solid electrolyte was obtained by pre-grinding at 100 rpm for 0.5h and ball milling at 450 rpm for 20h. The blank was cold pressed and placed in a quartz tube, heated to 450℃ at room temperature for 5h. The temperature was lowered to room temperature to obtain a ceramic phase high ionic conductivity sulfide solid electrolyte Li6(GeSi)0Sb1S5I. 100mg of solid electrolyte was weighed and placed in a battery mold, pressed at a pressure of 550MPa for 1min, and a battery long cycle test was carried out with Li-In as the negative electrode and NCM811 as the positive electrode at a current density of 0.1C. The test showed that the battery cycled 100 times and the capacity remained at 150 mAh g -1 .

[0058] Comparative Example 1

[0059] 0.670g Li2S, 0.285g GeS2, 0.058g Si, 0.141g Sb2S3, 0.1683g S, 0.6692g LiI raw materials with a molar ratio of 2.92: 0.417: 0.417: 0.083: 1.05: 1 were put into a ball mill (ball to material ratio was 20: 1). The amorphous phase mixture of sulfide solid electrolyte was obtained by pre-grinding at 100 rpm for 0.5h and ball milling at 450 rpm for 20h. The blank was cold pressed to obtain a blank, placed in a quartz tube, and heated to 450℃ at room temperature for 5h. The temperature was lowered to room temperature to obtain a ceramic phase high ionic conductivity sulfide solid electrolyte Li 41 / 6 (GeSi) 5 / 12 Sb 1 / 6 S5I. Weigh 100 mg of solid electrolyte and put it into the battery mold. Press it at 550 MPa for 1 min. Use Li-In as the negative electrode and NCM811 as the positive electrode at a current density of 0.1C to perform a battery long cycle test. The test shows that the battery cycled 100 times and the capacity remained at 80 mAh g -1 .

[0060] Comparative Example 2

[0061] 0.551g Li2S, 0g GeS2, 0g Si, 1.02g Sb2S3, 0.202g S, 0.6692g LiI raw materials with a molar ratio of 2.4:0:0:0.6:1.26:1 were put into a ball mill (ball to material ratio was 20:1). The amorphous phase mixture of sulfide solid electrolyte was obtained by pre-grinding at 100 rpm for 0.5h and ball milling at 450 rpm for 20h. The blank was cold pressed to obtain a blank, placed in a quartz tube, and heated to 450℃ at room temperature for 5h. The temperature was lowered to room temperature to obtain a ceramic phase high ionic conductivity sulfide solid electrolyte Li 29 / 5 (GeSi)0Sb 6 / 5 S5I. Weigh 100 mg of solid electrolyte and put it into the battery mold. Press it at 550 MPa for 1 min. Use Li-In as the negative electrode and NCM811 as the positive electrode at a current density of 0.1C to perform a battery long cycle test. The test shows that the battery cycled 100 times and the capacity remained at 20 mAh g -1 .

[0062] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A high ionic conductivity sulfide solid electrolyte, characterized in that: The general formula of the high ionic conductivity sulfide solid electrolyte is Li (7-x) (GeSi) (1-x) / 2 Sb x S5I, where 1 / 3≤x≤1.

2. The high ionic conductivity sulfide solid electrolyte according to claim 1, characterized in that: The ionic conductivity of the high ionic conductivity sulfide solid electrolyte is 1×10 -3 ~2×10 -2 S / cm.

3. The method for preparing the high ionic conductivity sulfide solid electrolyte according to any one of claims 1 to 2, characterized in that: The preparation method comprises: A mixture containing Li2S, Sb2S3, S and LiI is ball-milled and reacted to obtain the high ionic conductivity sulfide solid electrolyte.

4. The preparation method according to claim 3, characterized in that: The mixture also includes GeS2 and Si.

5. The preparation method according to claim 4, characterized in that: The molar ratio of Li2S, GeS2, Si, Sb2S3, S and LiI is: 2.5-3: 0-0.33: 0-0.33: 0.17-0.5: 1.05:

1.

6. The preparation method according to claim 3, characterized in that: The rotation speed of the ball mill is 300 to 500 rpm, and the ball milling time is 15 to 25 hours.

7. The preparation method according to claim 3, characterized in that: The pre-grinding is performed before the ball milling, the rotation speed of the pre-grinding is 100 to 300 rpm, and the pre-grinding time is 1 to 2 hours.

8. The preparation method according to claim 3, characterized in that: The reaction temperature is 400-500° C., and the reaction time is 3-7 hours.

9. Use of the high ionic conductivity sulfide solid electrolyte according to any one of claims 1 to 2 in a sulfide solid-state battery.

10. The use according to claim 9, characterized in that: The sulfide solid-state battery comprises a positive electrode, a negative electrode and a solid electrolyte; The solid electrolyte is a high ionic conductivity sulfide solid electrolyte; The positive electrode is selected from LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.6 Co 0.2 Mn 0.2 One of O2 and LiCoO2; The negative electrode is selected from at least one of Li-In alloy, Li-Mg alloy and Li-Sn alloy.

Citation Information

Patent Citations

  • Lithium-containing argyrodite solid electrolyte with dopant and preparation method of lithium-containing argyrodite solid electrolyte

    CN111430808A

  • Sulfide solid electrolyte, preparation method thereof and lithium ion battery

    CN113659199A

  • Argyrodite type sulfide solid electrolyte containing lithium halide coating layer and preparation of argyrodite type sulfide solid electrolyte

    CN114267874A

  • Solid electrolyte, preparation method thereof and battery containing electrolyte

    CN115986203A

  • Glassy state sulfide solid electrolyte material with high lithium iodide content as well as preparation method and application of glassy state sulfide solid electrolyte material

    CN116315056A